Effects of virtual reality technology on early mobility in critically ill adult patients: a systematic review and meta-analysis - Yansha He; Yansha He; Qin Yang; Xiaoxia Dai; Tian Chen; Huan Wu; Kunjie Li; Shiqiong Zhu; Yanlin Liu; Hua Lei (Frontiers in Neurology)
ObjectiveThe study aimed to explore the effects of virtual reality (VR) technology on motor function rehabilitation in critically ill patients.MethodsAdhering to the PRISMA systematic evaluation method for developing the literature ranking criteria and search strategy, the following databases were systematically searched: PubMed, Embase, Web of Science, the Cochrane Library, CNKI, Wanfang Data, Chinese Medical Journal Full-Text Database, and SINOMED. The search focused on the impact of virtual reality technology on limb function rehabilitation in critically ill patients, covering the period from the database’s inception to 6 December 2024. To evaluate the quality of the included studies, the risk of bias was assessed using the RevMan 5.4 tool.ResultsA total of 11 randomized controlled trials (RCTs) published over 10 years were included, involving 880 critically ill adult patients: 435 in the experimental group and 445 in the control group. The meta-analysis showed that, compared to the control group, virtual reality technology significantly improved the Berg Balance Scale (BBS) score (MD = 3.95, 95% CI: 3.19, 4.70, p < 0.05), the Functional Independence Measure (FIM) score (MD = 0.21, 95% CI: −1.35, 1.76, p > 0.05), the Functional Ambulation Category (FAC) score (MD = 0.72, 95% CI: 0.49, 0.94, p < 0.05), the upper limb motor function (Fugl-Meyer Assessment, FMA) score (MD = 5.08, 95% CI: 3.46, 6.69, p < 0.05), and the lower limb motor function (Fugl-Meyer Assessment FMA) score (MD = 2.83, 95% CI: 1.99, 3.67, p < 0.05) of the adult critically ill patients.ConclusionCompared to traditional rehabilitation techniques, virtual reality technology has a better overall effect in improving motor rehabilitation in critically ill patients and enhancing balance, functional walking, and upper and lower limb motor functions. However, the effect of enhancing the functional independence of limbs is not yet evident and still needs to be confirmed by high-quality, multicenter, and large-sample clinical trials.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/ Prospero register No.: CRD42024546409.